2011
DOI: 10.1186/1472-6963-11-86
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality of residents at admission to nursing home: A longitudinal cohort study

Abstract: BackgroundAn increasing numbers of deaths occur in nursing homes. Knowledge of the course of development over the years in death rates and predictors of mortality is important for officials responsible for organizing care to be able to ensure that staff is knowledgeable in the areas of care needed. The aim of this study was to investigate the time from residents' admission to Icelandic nursing homes to death and the predictive power of demographic variables, health status (health stability, pain, depression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
56
3
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 31 publications
(52 reference statements)
9
56
3
7
Order By: Relevance
“…We found an elevated mortality of institutionalized older adults [2], and the greater risk of death in the residential care setting compared to home-based care [8,9]. The results also confirm that ADL level is a very powerful predictive mortality factor [3].…”
supporting
confidence: 77%
See 1 more Smart Citation
“…We found an elevated mortality of institutionalized older adults [2], and the greater risk of death in the residential care setting compared to home-based care [8,9]. The results also confirm that ADL level is a very powerful predictive mortality factor [3].…”
supporting
confidence: 77%
“…Institutionalized dependent older adults represent a highly vulnerable group of the population, with high mortality as described in previous studies [1,2]. The Activities of Daily Living (ADL) level [3], cognitive impairment [4], hip fracture [5], cancer [6] and Chronic Obstructive Pulmonary Disease [7] are important risk factors of mortality in this population.…”
mentioning
confidence: 99%
“…10 Data investigating predictors of survival for anyone admitted into an aged care facility are limited. 17 A recent longitudinal study of 2206 admissions to Icelandic nursing homes reported significant predictors of survival included age, health stability, and activities of daily living (ADL) functioning. 17 Whereas many studies have analysed prognostic factors in palliative patients, 14,18-25 few have investigated predictors of shortened survival for those required to be discharged from a PCU to an RACF.…”
Section: Introductionmentioning
confidence: 99%
“…17 A recent longitudinal study of 2206 admissions to Icelandic nursing homes reported significant predictors of survival included age, health stability, and activities of daily living (ADL) functioning. 17 Whereas many studies have analysed prognostic factors in palliative patients, 14,18-25 few have investigated predictors of shortened survival for those required to be discharged from a PCU to an RACF. Lau et al, 25 in an unpublished retrospective audit of PCU separations over a 3-month period, investigated the addition of the Palliative Prognostic Score (PaP) to clinical predictive survival during discharge planning.…”
Section: Introductionmentioning
confidence: 99%
“…These survival rates are approximately 10–30% lower than those reported for more broadly defined populations of octogenarians and nonagenarians initiating dialysis 21 , and lower than overall rates reported for general NH populations 22,23 , although the lack of a relevant comparison group in most studies of ESRD residents makes it impossible to quantify the impact of ESRD on survival in a NH population. Survival does appear to be lower in patients newly started on dialysis, who may represent an important subgroup for future study or intervention.…”
Section: Discussionmentioning
confidence: 63%